Medicinal Plant Production System Management in Rural Java, Indonesia: Views of Local Actors from a Participatory Rural Appraisal Approach - Astutik, Sri; Ahimbisibwe, Vianny; Hintz, Kendisha Soekardjo; Purwanto, Purwanto; Humaedi, Muhammad Alie (Forest and Society, 2025)
Medicinal plants’ production systems in Indonesia’s rural Java play a crucial role in sustaining local livelihoods and healthcare needs. Medicinal plants are managed by locals independently based on household preferences and endowments through wild gathering and cultivation-based production systems. However, these situations create a continual problem of weak bargaining positions. Thus, this study aimed to assess local needs and potential in supporting medicinal plants production systems management in Java, Indonesia, with the view to advance local actors' perspectives in a multistakeholder platform. The Participatory Rural Appraisal (PRA) approach proved useful in incorporating local knowledge in the planning and development of strategies. We implemented PRA techniques, such as problem identification based on a cause-and-effect diagram, group discussion and brainstorming, preference ranking of priority species, and a Venn diagram based on stakeholders' classification. These were carried out with 150 local actors from four villages. Results reveal that Candlenut tree are the preferred species in the wild gathering system, while Javanese turmeric and Broadleaf plantain are preferred in the cultivation-based production systems. Urgent interests include more lucrative gathering and cultivation, a remunerative market, and a reliable local economic institution. The PRA results demonstrate that local actors' involvement is highly required in administering production systems to enhance medicinal plants’ sustainable production and management.